2017
DOI: 10.1590/s1984-29612017065
|View full text |Cite
|
Sign up to set email alerts
|

Potential of entomopathogenic nematodes of the genus Heterorhabditis for the control of Stomoxys calcitrans (Diptera: Muscidae)

Abstract: The present study verified the pathogenic potential of entomopathogenic nematodes (EPNs) of the genus Heterorhabditis (Heterorhabditis bacteriophora, isolate HP88 and Heterorhabditis baujardi isolate LPP7) to immature stages of Stomoxys calcitrans in the laboratory. All EPN concentrations of the H. bacteriophora HP88 strain caused mean larval mortality greater than 90% after four days. Higher concentrations of the H. baujardi LPP7 isolate (≥50 EPNs/larva) eliminated more than 70% of larvae after six days with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
3
12
3
Order By: Relevance
“…The aforementioned authors reported that a concentration of 200 infective juveniles of H. bacteriophora HP88 per S. calcitrans larva caused a mortality rate of 96.7% of the fly larvae, while in the present study, the mortality rate caused by H. bacteriophora HP88 at the same concentration was 91.7%. In addition, Leal et al (2017) reported that H. baujardi LPP7 caused a larval mortality rate of 93.3%, unlike in this study, in which the highest mortality rate caused by H. baujardi LPP7 was 35%. Despite the difference in periods of exposure in the two studies, H. bacteriophora HP88 resulted a mortality rate of more than 90% in both studies.…”
Section: Infection Of Stomoxys Calcitrans Larvae By Epns In Different Periods Of Exposurecontrasting
confidence: 90%
See 2 more Smart Citations
“…The aforementioned authors reported that a concentration of 200 infective juveniles of H. bacteriophora HP88 per S. calcitrans larva caused a mortality rate of 96.7% of the fly larvae, while in the present study, the mortality rate caused by H. bacteriophora HP88 at the same concentration was 91.7%. In addition, Leal et al (2017) reported that H. baujardi LPP7 caused a larval mortality rate of 93.3%, unlike in this study, in which the highest mortality rate caused by H. baujardi LPP7 was 35%. Despite the difference in periods of exposure in the two studies, H. bacteriophora HP88 resulted a mortality rate of more than 90% in both studies.…”
Section: Infection Of Stomoxys Calcitrans Larvae By Epns In Different Periods Of Exposurecontrasting
confidence: 90%
“…Despite the difference in periods of exposure in the two studies, H. bacteriophora HP88 resulted a mortality rate of more than 90% in both studies. Therefore, it can be stated that this EPN is highly virulent against stable fly larvae, because even though the exposure time in the present study was considerably shorter than that used by Leal et al (2017), H. bacteriophora HP88 was able to cause a larval mortality rate close to that reported by the aforementioned authors. However, H. baujardi LPP7 did not present same behavior, since Leal et al (2017) reported a mortality rate of 93.3% in 10 days of exposure, while the mortality rate in the present study after two days of exposure to H. baujardi LPP7 was only 35%.…”
Section: Infection Of Stomoxys Calcitrans Larvae By Epns In Different Periods Of Exposuresupporting
confidence: 66%
See 1 more Smart Citation
“…Entomopathogenic nematodes search for and locate their hosts by detecting products of excretion, CO 2 levels and temperature gradients. When a host is located, they penetrate through natural openings (mouth, anus and spiracles) or actively penetrate through the cuticle [182]. They then migrate into the hemocoel of the host [183] where their symbiotic bacteria release toxins that kill the host [184].…”
Section: Nematodesmentioning
confidence: 99%
“…The commercially available strain Steinernema feltiae produced the highest mortality in stable flies (56%) in laboratory bioassays on a hay/manure substrate [187]. Leal et al [182] demonstrated that Heterorhabditis spp. of nematodes show potential against stable fly larvae, but they have not been used in any commercial context to control stable flies to date.…”
Section: Nematodesmentioning
confidence: 99%